REVIEW OF ISLAMIC LAW REGARDING ON CONFISCATION OF ASSETS RESULTING FROM CRIMINAL ACTS OF CORRUPTION - M Dani Fariz Amrullah D; Dora Mustika; Ari Priyanto (Law Faculty of Universitas Bandar Lampung, 2025)
Corruption is an urgent problem that must be addressed immediately in order to achieve healthy economic growth. Various records show an increase and development of corruption models that occur. The mechanism for enforcing the law on corruption is something that must be considered because it ensures its implementation is correct, fair, there is no arbitrariness and no abuse of power. Corruption crimes when viewed from Islamic criminal law are included in jarimah. Jarimah or Jinayah comes from the word jarama-yajrimu-jarimatan, which means